A Holistic Perspective of Well-being: A Psycho - Spiritual Approach - Paul Rohan, J.C. (Satya Nilayam, 2023)
Wellbeing is the goal and final end of all creatures. Therefore it is common to all. However, in the human beings it is obvious that they can, by their reason and will, endanger their own wellbeing and that of others. In the natural level, wellbeing is holistic which incorporates all the spheres of a being in an integral sense. In an organism lower than the human beings, wellbeing includes every aspect of its being, whether it is physical or emotional or social necessity. The human beings due to various dichotomizations have segmented the holistic nature of wellbeing into physical, spiritual, social, economic and political realities. This paved the way to understand the unique and wholeness of the human wellbeing with many adjectives, as physical, spiritual, psychological, social, economic, etc. Currently a holistic view of wellbeing is being developed which is an integral and whole person model. It is called the psycho-spiritual approach which examines the interconnectedness of the psychological and spiritual dimensions of the human person. This paper after dealing with different types and theories of wellbeing analyses it in its psychological and spiritual domains. The combination of them is presented as psycho-spiritual wellbeing which is integral in its nature. Recent studies show that the psycho-spiritual approach is the conduit that can express sufficiently the holistic character of the concept of wellbeing. Such an integrated vision affirms the microcosmic character and the personhood of the human beings together with their potentials for self realization and self transcendence which are considered as the epitome of human wellbeing.
Keywords: Holistic; Dualism; Emotive; Positive Psychology; Self Transcendence; Existential